Plasmodesmata: structure and function (2006)
Plasmodesmata are channels that transverse the cell wall and membrane. These specialized and non passive channels act like gates that facilitate and regulate both communication and transportation of molecules such as water, nutrients, metabolites and macromolecules between plant cells. In the last decade a new point of view of plasmodesmata has emerged, and studies have  demonstrated that these channels are more complex. In this brief note, we pretend to expose the actual knowledge of plasmodesmata, focusing on their structure and function.